Numerical aspects of finite element simulations of residual stresses in metal matrix composites - Teixeira-Dias, F. (2001)
When a metal matrix composite (MMC) is cooled down from the fabrication or annealing temperature to room temperature, residual stresses are induced in the composite due to the mismatch of the thermal expansion coefficients of the matrix and reinforcement. A thermomechanical model describing these processes is presented considering that the reinforcement component has a thermo-elastic behaviour and that the matrix material exhibits a thermo-elastoviscoplastic behaviour. The model is implemented with a semi-implicit forward gradient finite element method algorithm and the resulting code is used to perform numerical simulations and calculate thermally induced residual stress fields in MMCs. Several tests are performed on a continuously reinforced MMC and a short cylindrical particle MMC in order to optimize the algorithm and define its governing parameters. Good agreement was obtained with results from other authors. Copyright © 2001 John Wiley & Sons, Ltd.